Resistance of detached-cells of biofilm formed by Staphylococcus aureus to ultra high pressure homogenization. (January 2021) - Zhang, Lingling; Zhu, Changqing; Chen, Xiaojing; Xu, Xinglian; Wang, Huhu
Graphical abstract: Highlights: UHPH could damage the cell membranes and morphology of S. aureus . Detached-cells of biofilm formed were more resistant to UHPH than planktonic cells. UHPH is potential non-thermal technology for reducing biofilm in liquid food. Abstract: Staphylococcus aureus is one of the main pathogens contributing to foodborne outbreaks, owing in part to its ability to form biofilms on food-contact surfaces. Cells that can detach from mature biofilms are a source for microbial cross-contamination in liquid food systems. The study was to evaluate and compare the resistance of detached-cells of biofilm formed by S. aureus and planktonic cells to Ultra High Pressure Homogenization (UHPH), a non-thermal technology applied in food processing. The results showed that the survival of both detached-cells and planktonic cells was dependent upon the applied pressure ranging from 30, 000 PSI to 40, 000 PSI, and cycle numbers with 1 and 3. A significant difference in UHPH resistance was observed at pressures of 35, 000 PSI to 40, 000 PSI whereby planktonic cell numbers were reduced about 2.0 log CFU/mL compared to a 0.5 log CFU/mL reduction of detached-cells. Cell resistance was further evaluated following UHPH by measuring membrane integrity and potential, as well as observing the cells using scanning electron microscopy (SEM). SEM images revealed more scattered exopolysaccharides in the biofilm after UHPH treatment compared to the control. Additionally, UHPH treatment resulted in planktonic cells having a greater shift to smaller cell size and a wider cell size distribution compared with detached-cells; this indicated a higher resistance of detached-cells to UHPH. This finding suggests that although UHPH has great potential application in food sterilization, the resistance of detached-cells cannot be ignored.